Modifikasi Atap Bangunan Untuk Pengendalian Risiko Serangan Kumbang Paedae - Dedy Kuswoyo; Julaikah Julaikah (Humanism: Journal of Community Empowerment (HJCE), 2023)
Tomcat is a beetle of the family Staphylinidae and genus Paederus sp. This beetle has been an outbreak of dermatitis in Indonesia. Islamic Boarding School X which is located in the Bantul district is one of the locations that have complaints about the incidence of Dermatitis Paederus, namely dermatitis caused by insects from the genus Paedarus or it can be called tomcat. Risk control efforts are needed to control hazards and reduce risks that may cause losses. One type of risk control effort that can be used effectively and with minimal direct involvement of humans is by using technical controls. This dedication control the attack of insects from the genus paedae and reduce the incidence of Dermatitis Paederus in Islamic boarding school students X, Bantul region. This activity was carried out using applied methods with direct application to building A of the Islamic boarding school X. Results: The ceiling installation was carried out at the Islamic boarding school with a total area of 50 square meters with the type of material used being Galvalume. The installation was carried out in all areas of the rooms at Pondok Pesantren X in Bantul Regency. Based on the results of an evaluation carried out using the interview method, 98% of respondents stated that ceiling installation was effective for controlling paedae beetle attacks and increasing room comfort.